Characterization of eating quality and starch properties of two Wx alleles japonica rice cultivars under different nitrogen treatments - Shuang-jie HUANG; Chun-fang ZHAO; Zhen ZHU; Li-hui ZHOU; Qing-huan ZHENG; Cai-lin WANG (Journal of Integrative Agriculture, 2020)
To understand the effect of nitrogen (N) fertilizer on rice (Oryza sativa L.) eating and cooking quality (ECQ). Here, we investigated the ECQ attributes, physicochemical foundation of ECQ, and amylopectin fine structure of two Waxy (Wx) alleles japonica rice cultivars Nanjing 9108 (NJ9108) and Huaidao 5 (HD5) under four N rates (0, 150, 300, and 450 kg ha−1). Sensory and pasting properties of the two cultivars varied depending on N rates. Compared with the control (0 kg ha−1), the overall eating quality and sensory value were significantly decreased under the N rates of 300 and 450 kg ha−1. Further, conventional descriptive analysis showed that the stickiness and retrogradation of cooked rice were significantly decreased. These results indicated that application of N fertilizer seems to affect the texture of cooked rice, causing it to be less sticky, lowering its retrogradation, and consequently reducing its palatability. Results from rapid visco analyzer (RVA) revealed that the peak and breakdown viscosities significantly decreased, while the setback viscosity and peak time increased under the N rates of 300 and 450 kg ha−1. However, no significant difference was observed when the N rate was 150 kg ha−1, indicating that less N fertilization can maintain rice ECQ. As the N rate increasing, protein content increased, whereas apparent amylose content, starch content, and gel consistency almost unchanged. Interestingly, compared with the control, under N treatments, the percentage of short amylopectin branches in NJ9108 was decreased, but increased in HD5, as controlled by amylopectin synthesis-related genes. Notably, SSI and BEIIb were down-regulated in NJ9108, whereas BEIIb was up-regulated in HD5. Thus, the palatability of both rice cultivars was significantly decreased under excessive N fertilization as a consequence of reduced stickiness and retrogradation of the cooked rice, which might have resulted from an elevated protein content and altered amylopectin fine structure. In addition, amylopectin synthesis appeared to be affected by N fertilizer and the genotype of the rice cultivar.